Black Swan in Phase Transfer Catalysis: Influence of Mixing Mode on the Stereoselectivity of Glycosylation. Issue 14 (25th February 2022) - Myachin, Ilya V.; Mamirgova, Zarina Z.; Stepanova, Elena V.; Zinin, Alexander I.; Chizhov, Alexander O.; Kononov, Leonid O.
Abstract: Phase transfer catalysis (PTC) is widely used for the preparation of anomerically pure aryl glycosides by glycosylation of phenols with glycosyl halides. Here, we attempted to synthesize 4‐(3‐chloropropoxy)phenyl (CPP) sialoside – a useful Janus glycoside for neoglycoconjugate synthesis. A batch glycosylation reaction under typical PTC conditions ( N ‐acetylsialyl chloride, 4‐(3‐chloropropoxy)phenol, Bu4 NHSO4, AcOEt, 10 % aq Na2 CO3 ) resulted in formation of CPP sialoside as a single anomer, albeit in low yield. Conversely, the PTC glycosylation in flow using Comet X‐01 micromixer doubled the yield of CPP sialoside, which was obtained as a mixture of anomers suggesting the change in the reaction mechanism apparently induced by the change in mixing mode. An increase in flow rate led to further loss of stereoselectivity while the use of T‐shaped mixer increased stereoselectivity. Similar results were obtained for N, N ‐diacetylsialyl chloride and two other para ‐alkoxy‐substituted phenols suggesting generality of the discovered phenomenon. Abstract : The influence of mixing mode on the outcome of the glycosylation under phase transfer conditions (batch vs flow) is found to be more complicated than it is generally assumed. A change in the way reagents are mixed leads not only to the enhanced mass transfer and consequently higher yield but also to a change in reaction mechanism.